2013
DOI: 10.1371/journal.pone.0073646
|View full text |Cite
|
Sign up to set email alerts
|

Wnt11b Is Involved in Cilia-Mediated Symmetry Breakage during Xenopus Left-Right Development

Abstract: Breakage of bilateral symmetry in amphibian embryos depends on the development of a ciliated epithelium at the gastrocoel roof during early neurulation. Motile cilia at the gastrocoel roof plate (GRP) give rise to leftward flow of extracellular fluids. Flow is required for asymmetric gene expression and organ morphogenesis. Wnt signaling has previously been involved in two steps, Wnt/ß-catenin mediated induction of Foxj1, a regulator of motile cilia, and Wnt/planar cell polarity (PCP) dependent cilia polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 80 publications
7
43
0
Order By: Relevance
“…3C), raising the question of whether laterality determination is affected by loss of Wnt5a and Wnt11. We have previously shown that PCP breaks bilateral symmetry by positioning cilia to the posterior side of the PNC cells (Nonaka et al, 2005;Song et al, 2010), and in Xenopus embryos knocking down Wnt11b results in left-right defects ( Walentek et al, 2013). In order to test whether Wnt5a and Wnt11 control PCP-regulated laterality determination, we examined asymmetric gene expression of Nodal and Pitx2 (Lowe et al, 1996;Logan et al, 1998).…”
Section: Wnt11mentioning
confidence: 99%
“…3C), raising the question of whether laterality determination is affected by loss of Wnt5a and Wnt11. We have previously shown that PCP breaks bilateral symmetry by positioning cilia to the posterior side of the PNC cells (Nonaka et al, 2005;Song et al, 2010), and in Xenopus embryos knocking down Wnt11b results in left-right defects ( Walentek et al, 2013). In order to test whether Wnt5a and Wnt11 control PCP-regulated laterality determination, we examined asymmetric gene expression of Nodal and Pitx2 (Lowe et al, 1996;Logan et al, 1998).…”
Section: Wnt11mentioning
confidence: 99%
“…Obviously, consistent geometrical orientation as an expression of planar cell polarity must be achieved during both prenatal and postnatal ciliogenesis [Jones et al, 2007;Wallingford, 2010;Wallingford and Mitchell, 2011]. Using various model organisms such as Drosophila and Xenopus , a close connection between the planar cell polarity signaling pathway, cell division and migration, the cytoskeleton and the assembly of cilia has been demonstrated during embryogenesis [Hayes et al, 2007;Kim et al, 2010;Goodrich and Strutt, 2011;Kim et al, 2012;Walentek et al, 2013]. These interrelationships are of particular relevance with regard to breaking symmetry at the beginning of left-right patterning of the body plan.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of PCP-mediated morphogenetic processes requires non-canonical Wnts as ligands, and Wnt11 has been identified as one of the primary PCP ligands during zebrafish and Xenopus gastrulation (Heisenberg et al, 2000; Li et al, 2008; Schambony and Wedlich, 2007; Tada and Smith, 2000; Walentek et al, 2013). The potential role of Wnt11 as a PCP ligand in mammals, however, has remained less clear because Wnt11 mutant mice do not display some of the characteristic phenotypes observed consequent to mutation of core PCP genes Vangl2, Dvl and Celsr .…”
Section: Discussionmentioning
confidence: 99%
“…In Xenopus and zebrafish, Wnt5a and Wnt11 have been identified as two primary ligands capable of activating non-canonical Wnt/ PCP signaling to regulate tissue morphogenesis during gastrulation (Heisenberg et al, 2000; Kilian et al, 2003; Tada and Smith, 2000; Walentek et al, 2013; Wallingford et al, 2001), although in other context they can also activate canonical Wnt signaling (Cha et al, 2008; Cha et al, 2009; Tao et al, 2005). During gastrulation, Wnt11 acts in both cell-autonomous and cell-non-autonomous fashion to regulate polarized cell intercalation and directional migration of mesodermal and endodermal cells (Heisenberg et al, 2000; Ulrich et al, 2003; Witzel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation